Single-walled carbon nanotubes toxicity to the freshwater amphipod Hyalella azteca: influence of sediment and exposure duration - Messika Revel; Michel Fournier; Pierre Yves Robidoux (MDPI AG, 2015)
Carbon nanomaterials are present in various industrial applications and therefore their release into the environment including freshwater ecosystem is expected to increase. The aim of the present study was to investigate the influence of several parameters on the toxicity of single-walled carbon nanotubes (SWCNT) to the freshwater amphipod, Hyalella azteca. The effect of period of exposure, sediment presence and possible impurities released during SWCNT preparation on survival and/or growth of such organism was evaluated. We measured a reduction of survival at concentrations ranging from 10 to 40 mg/L after 96-h exposure, while no mortality was observed with the same concentrations and in the presence of artificial sediment after 14 days of exposure. It is possible that SWCNT are adsorbed on the organic matter from the artificial sediment leading to a decrease of SWCNT bioavailability. The survival and growth toxicity tests revealed a stronger effect at 28 days compared to the 14 days of exposure, and full mortality of organisms at 1000 mg/L for both exposure times. The presence of SWCNT in the gut of survived organisms was observed. The present study demonstrates that the interaction with sediment should be considered when carbon nanotubes toxicity through water exposure is investigated.